2016
DOI: 10.1109/tasc.2016.2555910
|View full text |Cite
|
Sign up to set email alerts
|

High-Tc Step-Edge Josephson Junction Arrays: Comparison of Simulated and Experimental Voltage Responses

Abstract: With the recent development of multi-junction Superconducting Quantum Interference Device (SQUID) arrays and Superconducting Quantum Interference Filters (SQIFs) using High Temperature Superconducting (HTS) materials, it has become increasingly desirable to accurately model HTS devices to enable the optimization of the design for enhanced performance before fabrication. Initially, to develop our simulation capability for HTS devices, we have been working with a commercial software package to fit the data obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, the average voltage modulation per SQUID within each sub-array was only ~1 μV, which was smaller than a single SQUID loop of the same area. More recently, in terms of biasing the arrays, Hannam et al [20] reported different voltage-magnetic field responses depending on the method of current biasing the arrays when modelling the effect of biasing geometries.…”
Section: Schultze Et Almentioning
confidence: 99%
“…However, the average voltage modulation per SQUID within each sub-array was only ~1 μV, which was smaller than a single SQUID loop of the same area. More recently, in terms of biasing the arrays, Hannam et al [20] reported different voltage-magnetic field responses depending on the method of current biasing the arrays when modelling the effect of biasing geometries.…”
Section: Schultze Et Almentioning
confidence: 99%
“…The methods established to use FastHenry and JSIM for small arrays with narrow tracks can be extended to any type and size of array, with any bias connection points, like the two small test arrays with loops of unequal areas in [92], shown in figure 18.…”
Section: Small Arrays Of Loops Of Unequal Areamentioning
confidence: 99%